Identifying influential factors in the sustainable reconstruction of residential complexes after war; cade study: Syria - Hanin Weshah; Hanieh Sanaeian; Mohammadali KHanmohammadi (مسکن و محیط روستا)
War has significant negative impacts not only on human societies but also on the environment. In Syria, the residential sector has been heavily affected by extensive destruction, which needs to be prioritized in reconstruction strategies and plans in order to provide necessary housing for displaced individuals. This research aims to propose sustainable housing reconstruction strategies after war in Syria. Studies conducted on the literature and case studies from war-torn countries show that reconstruction can be an opportunity for achieving sustainable development, as long as it is considered within long-term development plans. This article focuses on finding new perspectives and solutions for the sustainable reconstruction of partially destroyed residential units after war. To achieve this goal, we first define the concept of reconstruction and its approaches, then examine the indigenous housing architecture of Damascus and study global experiences in post-war reconstructions in different countries. Considering the conditions of each country and assessing the post-war situation in Syria, particularly in the city of Damascus, an appropriate strategy for reconstruction can be chosen.To achieve this goal, a residential complex that has been affected by war in Syria was selected and examined. In this regard, fieldwork and questionnaires were conducted to identify the key components in sustainable housing reconstruction projects after war, in line with the research framework. By using the questionnaire, the opinions of experts on the most influential components in such projects were obtained. The results of the questionnaire show that these components are more important in environmental dimensions and subsequently in social dimensions, but less important in economic dimensions. Ultimately, the components of environmental sustainability and social sustainability are prioritized.